Motivasi dan Persepsi Kepala SMP Adiwiyata di Kepulauan Riau - Parida; Maisah; Widdah, Minnah El (Indra institute Research & Publication, 2024)
Leadership is an important element in achieving, maintaining and improving organizational performance. As the focus of this study, the researcher investigated the impact of motivation and perception of SMPN principals on the achievement of Adiwiyata schools in the Riau Islands. The research method used is a quantitative research approach with a field survey method. The population of this study was SMPN Pembinaan Adiwiyata schools in the Riau Islands which have the same level of accreditation and status as Adiwiyata. The research data were collected by distributing questionnaires that were tested for validity and reliability. The tool needed to reveal the variables is a questionnaire using a Likert scale. The results of this study indicate that work motivation has a partial effect on manager perceptions. In addition, a significant partial effect was found between work motivation and manager perceptions. The conclusion of this study is that high staff work motivation determines the principal's perception and the success of Adiwiyata schools.